Infectious hematopoietic necrosis virus (IHNV) nucleoprotein amino acid residues affect viral virulence and immunogenicity in rainbow trout (Oncorhynchus mykiss). Issue 130 (November 2022) - Li, Jiahui; Xia, Dong; Zhang, Mengmeng; Zhang, Yanru; Liu, Xuefei; Sun, Jinhui; Xu, Baoxing; Yang, Jiawei; Wang, Na; Shi, Wen; Guan, Xueting; Liu, Min
Abstract: This study compared the N protein sequences of genotype J with other genotypes of IHNV to select amino acid residues that may be related to the change in viral virulence. The recombinant viruses containing different mutation sites were rescued by alanine scanning mutagenesis and the reverse genetic system. The nine recombinant virus strains obtained in this work were named rIHNV-N85, rIHNV-N102, rIHNV-N146, rIHNV-N380, rIHNV-N85-102-146, rIHNV-N85-102-380, rIHNV-N85-146-380, rIHNV-N102-146-380, and rIHNV-N85-102-146-380 . Pathogenicity and immunity assays were performed to determine the role of virulence sites. The result of the pathogenicity test showed that the survival rates of rIHNV-N85, rIHNV-N102, rIHNV-N85-102-146, and rIHNV-N85-102-380 groups were 52.5%, 55%, 67.5%, and 57.5%, while the survival rate of wild-type (wt) IHNV HLJ-09 group was only 10%. The replication ability of recombinant viruses with substitutions at positions 85 and 102 was significantly inhibited in vivo and in vitro . The qRT-PCR result indicated that the cytokines of IFN1, IL-8, and IL-1β expression levels were increased in rIHNV-N85, rIHNV-N102, rIHNV-N85-102-146, and rIHNV-N85-102-380 groups. In addition, these four recombinant viruses could cause the rainbow trout to produce anti-IHNV-specific antibodies immunoglobulin M (IgM) earlier, confirming that 85 and 102 amino acid residues of N protein affected the virulence and immunogenicity of IHNV. All these results suggest that mutations of the N protein virulence sites reduce virulence while retaining immunogenicity. This also provides a new idea for studying the virulence mechanism of rhabdoviruses and preparing attenuated vaccines. Highlights: Nine rIHNVs with N protein site mutations were rescued by reverse genetics. Mutants in N protein attenuated IHNV replication. Amino acid residues 85 and 102 in N protein were important sites affecting the virulence and immunogenicity of IHNV. This study provides a new idea for studying the virulence mechanism of rhabdoviruses and preparing attenuated vaccines.